If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10 + -3z = 6z + -8z Combine like terms: 6z + -8z = -2z -10 + -3z = -2z Solving -10 + -3z = -2z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '2z' to each side of the equation. -10 + -3z + 2z = -2z + 2z Combine like terms: -3z + 2z = -1z -10 + -1z = -2z + 2z Combine like terms: -2z + 2z = 0 -10 + -1z = 0 Add '10' to each side of the equation. -10 + 10 + -1z = 0 + 10 Combine like terms: -10 + 10 = 0 0 + -1z = 0 + 10 -1z = 0 + 10 Combine like terms: 0 + 10 = 10 -1z = 10 Divide each side by '-1'. z = -10 Simplifying z = -10
| 4x-4+2x-16=360 | | 16x=5-5x | | -1+c+9=4c+8 | | -4-3k=-k+8 | | 260-y=105 | | t-34=48 | | 220=135-y | | -5j=3-8j | | I-26I= | | k=-6j | | -2m=8-m | | (x+8)(4x+3)=0 | | x^4+x^3+8x-8=0 | | 9p-6=10p-9 | | -6c=c-7 | | -9f=-8f-9 | | 3h-10=-25 | | 6(c-2)=(c-6) | | 2x-472/x^2 | | 2u=3u-9 | | 63=17v-8v | | x+(x*0.07)-(x*0.03)=20000 | | 2xsquared+y=3x-1 | | -4u+8=2u+8-6u | | 5.8x+4.35(147-x)=759.80 | | -9z+8=-10-6z | | 4-(5-7x)=2(x-1) | | 5.6x+4.15(155-x)=767.95 | | 17y-9y=72 | | -4z-8=12 | | 10x+89=61 | | k=-12j |